Comparison of FAIM3 gene expression between new cases of ALL and relapsed ALL - rezvani, mohammad reza (Archives of Medical Laboratory Sciences, 2020)
Background: Acute lymphoblastic leukemia (ALL) is one of the major lymphoid malignancies and the most common hematologic malignancy in children. ALL is characterized by the presence of malignant lymphoblasts in the blood so that immature lymphocytes cannot become mature and thus do not have an adult cell function. Although it is not unusual in adults, it usually affects children. Most children with this disease are recovered from therapeutic protocols. But the relapse is common after recovery or during the treatment. Various factors are supposed to contribute to the relapse of the disease. One of these factors that is likely to be effective in the recurrence of ALL is the FAIM3 protein (an FCuR), or the Fas inhibitory molecule-3 (FAIM3). The aim of this study was to investigate FAIM3 (TOSO) as a new prognostic factor in ALL. Materials and methods: In this study, 19 patients with newly diagnosed and 17 patients with relapsed ALL were included. FAIM3 gene expression was measured with the qRT-PCR method. Results: The expression level of FAIM3 in relapsed patients was 5.44 folds higher than newly diagnosed ALL patients. Conclusion: Prognosis of ALL is usually well-proven in children and can be cured. However, recurrence of the disease is common. At the molecular level, there are several factors that are referred to as the "factor involved in the relapse" of the disease. These factors increase the survival of the leukemic cells. According to the results of the present study, gene expression level of FAIM3 as an anti-apoptotic factor has increased in relapsed ALL lymphoblasts, compared with new diagnosed patients. Therefore, FAIM3 can be considered as a contributing factor in the relapse of the disease.